Effect of Application of Liquid Organic Fertilizer from Vegetable and Fruit Waste on Lettuce Plants (Lactuca Sativa L.) - Novriyansyah, Eko Abadi (PT. Riset Press International, 2025)
Sustainable agriculture is an agricultural system that has the LEISA (Low External Input Sustainable Agriculture) principle, namely by preserving the environment and preserving ecosystem space. The use of fruit and vegetable waste to make liquid organic fertilizer contains N, P and K which are good for plant growth. Liquid organic fertilizer formula from a mixture of vegetable waste, fruit waste and fish waste to enrich the content of macro nutrients and micro nutrients, so that it becomes a complete fertilizer for plants. This research aims to test the application of liquid organic fertilizer from urban organic waste on the growth and production of lettuce plants. The research method used was a Randomized Block Design (RAK) with one factor, with 5 treatments and repeated 3 times. The treatment given was a dose of liquid organic fertilizer derived from vegetable and fruit waste, namely P0 0 ml/ L, P1 20 ml/ L, P2 40 ml/ L, P3 60 ml/ L, P4 80 ml/ L. Observations included element content macro nutrients N, P, K, pH, Mo, and Fe in liquid organic fertilizer, plant height (cm), number of leaves (strands), and harvest weight (gr). The results of this research show that the liquid organic fertilizer content of vegetable and fruit waste analyzed is in accordance with SNI Kepmentan 261 of 2019. The application of liquid organic fertilizer from vegetable and fruit waste has a significant effect on the variables of plant height, number of leaves and harvest weight observed. The optimum dose of liquid organic fertilizer from vegetable and fruit waste for lettuce plants is 60ml/L/polybag.